KEANEKARAGAMAN JENIS BENALU PEMARASIT PADA TANAMAN DI KEBUN RAYA BATURRADEN DAN SEKITARNYA - Sunaryo .; Tahan Uji (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Benalu is one of the parasitic plant group which have been ataccked to many plantsspecies in Baturraden Botanical Garden and its vacinity. Exploration and collection of parasitic plants species in this area are conducted. Five parasitic plants species, i.e.Dendropthoe curvata, Dendropthoe pentandra, Macrosolen cochinchinensis, Scurrula lepidota and Scurrula parasitica are recorded to parasiting 18 plants species in this area. Dendropthoe pentandra is reported as the highest population species to parasiting plants species. While the plants species of Myrtaceae and Lauraceae families are also reported as the highest species parasited.Key words : diversity – mistletoe – Baturraden Botanic Garden and its vacinity